The Adventures of a Boy Reporter - Morrison, Harry Steele, 1880- (Salt Lake City, UT : Project Gutenberg, 2004)
"The Adventures of a Boy Reporter" by Harry Steele Morrison is a novel written in the early 20th century. The story follows the ambitious young protagonist, Archie Dunn, who dreams of greater things beyond his small-town life. As he endeavors to become a reporter, the narrative showcases his journey from rural innocence to the bustling streets of New York City, highlighting his adventures and mishaps along the way. The beginning of the book introduces Archie as a boy filled with dreams and aspirations, set against the backdrop of his rural upbringing. Through conversations between the local mothers, we learn about Archie$1 (Bs formation of the (3z(BHut Club(3y (Bwith his friends and their exciting plans to engage with the impending circus's arrival. However, Archie feels confined and longs for adventure, which ultimately leads him to undertake a daring decision to leave home for New York City. The opening sets the stage for his daring journey filled with trials and tribulations, as he navigates both the challenges of city life and the pursuit of his ambitions. (This is an automatically generated summary.)s
Release date is 2004-01-01
Produced by Jim Weiler, and David Widger
Keywords: Reporters and reporting -- Juvenile fiction